Local Experiences, Search, and Spillovers in the Housing Market - GARGANO, ANTONIO; GIACOLETTI, MARCO; JARNECIC, ELVIS (Journal of Finance, 2023)
ABSTRACT Recent local price growth explains differences in search behavior across prospective homebuyers. Those experiencing higher growth in their postcode of residence search more broadly across locations and house characteristics, without changing attention devoted to individual sales listings, and have shorter search duration. Effects are stronger for homeowners, in particular those living in less wealthy areas and looking for a new primary residence. We use reduced‐form analysis and a quantitative equilibrium model to show that the expansion of search breadth translates into widespread spillovers onto house sales prices and inventories of listings across postcodes within a metropolitan area.